Profile of fungal infections in the post-pandemic period in a hospital in Campos Gerais (Research, Society and Development, 2024)
Introduction: Healthcare-associated infections cause public health problems worldwide, and fungi have increasingly stood out in this context, especially after the COVID-19 pandemic and the alert regarding the spread of the potentially multidrug-resistant species Candida auris. Objective: to determine the profile of healthcare-associated fungal infections in the post-pandemic period. Methodology: This is a retrospective cross-sectional study carried out by collecting patient data from electronic medical records in a hospital in southern Brazil. Results: The prevalence of fungal infections was 6%, higher in females (68.5%), with a mortality rate of 74% and association with multiple comorbidities, invasive devices, antibiotic therapy, and corticosteroid therapy. The most prominent species was Candida albicans, which represented 47.4% of all infections, in addition to a rare case of infection by Saccharomyces cerevisiae and no Candida auris strain being isolated. The use of antibiotics was present in 93.2% of patients, antifungals in 30.1%, and corticosteroids in 38.4%. Conclusion: Fungal infections associated with healthcare were associated with the profile of elderly patients, presence of comorbidities, hospitalization in intensive care unit beds and presented a high mortality rate.